Structural equation model-based performance measurement system for transferring PPP water projects: a China perspective - Chen, Chuan; Liu, Jinchan; Zhang, Lanqian; Huang, Lin (Journal of Civil Engineering and Management, 2024)
A series of performance measurement need to be carried out throughout the project life cycle to ensure the successful transfer of public-private partnership (PPP) assets and meet stakeholder needs. More and more water projects are stepping into the transfer phase, but less studies carry out in-depth and systematic discussion on the performance measurement of PPP water projects at the transfer phase. Hence, to fill this gap, this research establishes a new performance measurement system (PMS) for evaluating the performance of the PPP projects stepping into the transfer phase based on the key performance indicators (KPIs). Through case study, expert interview and questionnaire, this paper formulates the logical basis behind PPP water projects at the transfer phase and subsequently constructs the transfer performance measurement system (TPMS) of these projects. Then, it conducts a confirmatory analysis of the impact relationship between the indicators based on structural equation modeling (SEM). Findings of expert interview and questionnaire indicate that there are 7 primary and 26 secondary indicators, and the model has a good fit. The TPMS will provide governments, operators and other stakeholders with a comprehensive and complete understanding as to indicators required of an effective performance measurement of PPP water projects.